The Eruption of Submarine Rhyolite Lavas and Domes in the Deep Ocean – Havre 2012, Kermadec Arc - Ikegami, Fumihiko; McPhie, Jocelyn; Carey, Rebecca; Mundana, Rhiannan; Soule, Adam; Jutzeler, Martin (Frontiers in Earth Science, 2018)
Silicic effusive eruptions in deep submarine environments have not yet been directly observed and very few modern submarine silicic lavas and domes have been described. The eruption of Havre caldera volcano in the Kermadec arc in 2012 provided an outstanding database for research on deep submarine silicic effusive eruptions because it produced 15 rhyolite (70-72 wt% SiO2) lavas and domes with a total volume of ~0.21 km3 from 14 separate seafloor vents. was first detected when extensive rafts of floating pumice appeared in satellite images taken on the 18th July. Moreover, in 2015, the seafloor products were observed, mapped and sampled in exceptional detail (1-m resolution AUV Sentry and ROV Jason2 deployed from R/V Roger Revelle). This survey revealed that as well as the pumice raft, the 2012 eruption had produced 15 rhyolite (70-72 wt% SiO2) lavas and domes with a total volume of ~0.21 km3 from 14 separate seafloor vents.